Néel Vector Induced Manipulation of Valence States in the Collinear Antiferromagnet Mn2Au - Elmers, H. J.; Chernov, S.; D'Souza, S. W.; Bommanaboyena, S. P.; Bodnar, S. Yu; Medjanik, K.; Babenkov, S.; Fedchenko, O.; Vasilyev, D.; Agustsson, S. Y.; Schlueter, C.; Gloskovskii, A.; et al. (ACS nano, 2020)
The coupling of real and momentum space is utilized to tailor electronic properties of the collinear metallic antiferromagnet Mn2Au by aligning the real space Néel vector indicating the direction of the staggered magnetization. Pulsed magnetic fields of 60 T were used to orient the sublattice magnetizations of capped epitaxial Mn2Au(001) thin films perpendicular to the applied field direction by a spin-flop transition. The electronic structure and its corresponding changes were investigated by angular-resolved photoemission spectroscopy with photon energies in the vacuum-ultraviolet, soft, and hard X-ray range. The results reveal an energetic rearrangement of conduction electrons propagating perpendicular to the Néel vector. They confirm previous predictions on the origin of the Néel spin-orbit torque and anisotropic magnetoresistance in Mn2Au and reflect the combined antiferromagnetic and spin-orbit interaction in this compound leading to inversion symmetry breaking.
CRIS-Team Scopus Importer:2023-03-27
Keywords: antiferromagnetism; arpes; electronic structure; harpes; momentum microscopy; photoemission; topology